Tolerance of local gogo rice sprouts under salinity stress conditions - Samudin, Sakka; Made, Usman; Maemunah, Maemunah; Jeki , Jeki; Mustakim, Mustakim (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
The expansion of rice planting areas in the future needs to be carried out outside Java, as fertile land in Java is shrinking due to land conversion. Most of the land outside Java consists of marginal land, such as areas with high salinity. High salinity levels in the soil cause a decrease in plant germination, growth, and production. The research aimed to examine the tolerance of each cultivar at each level of NaCl concentration, to obtain cultivars that were tolerant to salinity stress, and to determine the NaCl concentration that suppresses the germination of local upland rice. The research was structured using a completely randomized design with a two-factor factorial pattern. The first was the six upland rice cultivars, namely, dongan, jahara, Pulu Konta, pomegranate, kalendeng, and pulu tau leru, while the second factor was the NaCl concentration consisting of 0%, 0.2%, 0.4%, 0.6%, 0.8% and 1%. Thus, there were 36 experimental units, which were repeated three times so that there were 108 experimental units. The results of the research showed that there was no interaction with all germination variables; cultivar and concentration had a significant effect on maximum growth potential, germination capacity, germination time, plumule length, radicle length and dry weight of sprouts, while cultivar affected the wet weight of sprouts. Kalendeng has a high salinity tolerance. The use of NaCl concentrations of up to 0.6% has been able to reduce the germination capacity of local upland rice. The conclusion of the research showe that there was no interaction between all germination variables.